2002
DOI: 10.1051/gse:2002003
|View full text |Cite
|
Sign up to set email alerts
|

A further look at quantitative trait loci affecting growth and fatness in a cross between Meishan and Large White pig populations

Abstract: -A detailed quantitative trait locus (QTL) analysis of growth and fatness data from a three generation experimental cross between Large White (LW) and Meishan (MS) pig breeds was carried out to search for sex × QTL interactions, imprinting effects and multiple linked QTLs. A total of 530 F 2 males and 573 F 2 females issued from 6 F 1 boars and 23 F 1 sows were typed for a total of 137 markers covering the entire porcine genome. Nine growth traits and three backfat thickness measurements were analysed. All ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Alignment between pig chromosome 9 on RH map and human maps on USDA-MARC Pig Database [23], we found some QTLs associated with meat quality and production traits in this region such as body weight at 10 weeks of age (87 cM) [24], average backfat thickness (79.3-90 cM) [25], total saturated fatty acids (61.5-83.3 cM) [26], backfat at tenth rib (96-79 cM) [27]. Also, PDK4 had thought to be a key regulatory enzyme involved in switching the energy source from glucose to fatty acids in response to physiological conditions [17].…”
Section: Discussionmentioning
confidence: 92%
“…Alignment between pig chromosome 9 on RH map and human maps on USDA-MARC Pig Database [23], we found some QTLs associated with meat quality and production traits in this region such as body weight at 10 weeks of age (87 cM) [24], average backfat thickness (79.3-90 cM) [25], total saturated fatty acids (61.5-83.3 cM) [26], backfat at tenth rib (96-79 cM) [27]. Also, PDK4 had thought to be a key regulatory enzyme involved in switching the energy source from glucose to fatty acids in response to physiological conditions [17].…”
Section: Discussionmentioning
confidence: 92%
“…1999; Milan et al. 2002), but the existence of more than one QTL cannot be ruled out (Rohrer 2000; Quintanilla et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The best marker order of the ADRP gene between linked markers produced by a multipoint linkage analysis: SW2185-13.0-ADRP-5.0-SW1970-18.0-SW974 (numbers between markers indicate distance, cM). Several studies have reported QTL affecting growth and fat deposition traits in this region containing the porcine ADRP locus (Knott et al 1998;Rohrer & Keele 1998;De Koning et al 1999;Bidanel et al 2001;Quintanilla et al 2002).…”
Section: Resultsmentioning
confidence: 99%